"Does the voice in your head get kinder as you get older?" Women's perceptions of body image in midlife. (2nd September 2016) - Rodgers, Rachel F.; Paxton, Susan J.; McLean, Siân A.; Damiano, Stephanie R.
ABSTRACT: This study aimed to identify attitudes and reactions toward physical changes in midlife women. A Facebook thread, presenting a series of comments related to an initial statement, instigated by a radio program was analyzed. The thread contained 87 responses to the question "Does the voice in your head get kinder as you get older?" Content analysis revealed positive (56%) and negative (40%) comments and four themes: physical changes with aging, the decreased importance of physical appearance, the importance of sociocultural influences, and the invisibility of women in midlife. Findings revealed both positive and negative body image experiences in women related to midlife and have implications for prevention.